2022
DOI: 10.3390/en15145162
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of Coreless Axial Flux Permanent Magnet Machine with Novel Composite Structure Coils

Abstract: In this paper, a type of novel composite structure coil applied in the coreless stator is proposed and studied to improve the output performance and efficiency of the axial flux permanent magnet (AFPM) machine. In which the effective conductor is changed to be wedge-shaped by the rolling technology so that the turns of coils and filling factor can be further increased, and the ends are kept in the cylinder with a larger diameter to reduce the DC copper loss. Meanwhile, the air region between the double rotors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…During the measurements, the rotor rotated at 2150 rpm and was loaded with a torque of 0 to 3.51 Nm. The test bench for the motor load test is shown in Figure 12, with a converter (1) to supply the motor under test (2), an MT5 torque sensor to measure torque and speed (3) and an eddy current brake (4). Measurements of electrical quantities were performed using a class A power quality analyser.…”
Section: Sintered Magnetsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the measurements, the rotor rotated at 2150 rpm and was loaded with a torque of 0 to 3.51 Nm. The test bench for the motor load test is shown in Figure 12, with a converter (1) to supply the motor under test (2), an MT5 torque sensor to measure torque and speed (3) and an eddy current brake (4). Measurements of electrical quantities were performed using a class A power quality analyser.…”
Section: Sintered Magnetsmentioning
confidence: 99%
“…These machines, in relation to machines with a core, are characterised, among other things, by lower unit costs, no cogging torque and low winding inductance. Furthermore, due to the lack of a laminated steel sheet core, less waste is generated in the production of these machines, and at the end of their useful life, it is easier to dispose of and recover useful materials [3,4]. An increasing number of articles, for example [1,5], have presented the results of research related to the development of new designs of electric machines for specific applications.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of skew angle, overhang, or end coils in machines with 3D flux pathways, such as axial flux PM machines (AFPM), has revealed that 2D models and analytical methods are not sufficiently accurate [7,[11][12][13][14]. A detailed modelling of the machine is required in any case to study the eddy current losses in the stator winding.…”
Section: Introductionmentioning
confidence: 99%